PENGARUH CELEBRITY ENDORSER DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN MELALUI BRAND AWARENESS DI MIE ACEH KEDAI KIKO JAKARTA - Nur Chotimah; Rivera Silitonga (Panorama Nusantara, 2022)
This research is to determine the impact of celebrity endorsers and word of mouth on purchasing decisions through brand awareness at Mie Aceh Kedai Kiko Jakarta. The population in this study were buyers to Kedai Mie Aceh Kiko Jakarta with 200 participants. The sampling technique used in this study is purposeful sampling. This study uses a quantitative descriptive method to conduct research based on survey data by distributing questionnaires to respondents and the analytical method used by the author in this study is path analysis. The author used a quantitative descriptive method that is by analyzing the data using IBM SPSS Statistics 26. The results show that Word of mouth has a significant effect on Brand awareness, Celebrity endorserhas a significant effect on Brand awareness, Word of mouth and Brand awareness has a significant effect on Purchase Decisions, but Celebrity endorserhas no significant effect on Purchase Decisions at Mie Aceh Kedai Kiko Jakarta. Celebrity endorsers have an indirect effect on purchasing decisions through Brand awareness with a contribution of 0.065. Word of mouth has an indirect effect on purchasing decisions through Brand awareness with a contribution of 0.182.